2020
DOI: 10.3390/pharmaceutics12121171
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Based Therapeutics: Preclinical and Clinical Investigations

Abstract: Drug nanoformulations hold remarkable promise for the efficient delivery of therapeutics to a disease site. Unfortunately, artificial nanocarriers, mostly liposomes and polymeric nanoparticles, show limited applications due to the unfavorable pharmacokinetics and rapid clearance from the blood circulation by the reticuloendothelial system (RES). Besides, many of them have high cytotoxicity, low biodegradability, and the inability to cross biological barriers, including the blood brain barrier. Extracellular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 172 publications
(252 reference statements)
0
63
0
Order By: Relevance
“…For example, cationic nanoparticles can induce cell shrinkage, and vacuolation of the cytoplasm, leading to reduced cell viability [ 31 , 32 , 33 , 34 ]. On the contrary, preclinical and clinical EV studies have demonstrated negligible cytotoxicity and limited immunogenicity [ 13 , 35 , 78 , 79 ]. In this study, the viability of Raw264.7 cells in response to Cas9-loaded PULSin (cationic nanoparticle) and Cas9-loaded EVs was compared.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cationic nanoparticles can induce cell shrinkage, and vacuolation of the cytoplasm, leading to reduced cell viability [ 31 , 32 , 33 , 34 ]. On the contrary, preclinical and clinical EV studies have demonstrated negligible cytotoxicity and limited immunogenicity [ 13 , 35 , 78 , 79 ]. In this study, the viability of Raw264.7 cells in response to Cas9-loaded PULSin (cationic nanoparticle) and Cas9-loaded EVs was compared.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the inherent features of exosomes such as high bioavailability, exceptional biocompatibility, and low immunogenicity, exosomes are promising drug delivery candidates for intercellular communication. These features have resulted in exosomes attracting therapeutic attention in recent years ( 136 ). A significant issue associated with COVID-19 treatment lies in early detection, which is imperative to help reduce COVID-19 patient mortality.…”
Section: Therapeutic Strategy Of Using Exosomes For Treating Covid-19mentioning
confidence: 99%
“…Specific properties of EVs such as biocompatibility, biological barrier crossing, selective targeting, and the possibility to be modified make these vesicles a very promising basis for the development of novel therapies [5,6]. Importantly, EVs convey effects of cell therapy without presenting the same hazard as live cells, such as the case for EVs from mesenchymal stem cells (MSC-EVs) [45].…”
Section: Main Proposed Functions Of Extracellular Vesiclesmentioning
confidence: 99%
“…Apart from being active players in various biological processes [2,3], EVs have been identified as important means of communication alongside the nephron [4]. Furthermore, owing to their versatile characteristics, EVs represent a potential basis for the development of novel therapies [5,6]. Thus, EVs derived from mesenchymal stem cells (MSCs) have emerged as a powerful cell-free therapy for a variety of disease states, renal fibrosis being one of them [7].…”
Section: Introductionmentioning
confidence: 99%